CuII-selective bispidine-dye conjugates - Brox, Dominik; Comba, Peter; Herten, Dirk-Peter; Kimmle, Esther; Morgen, Michael; Rühl, Carmen L.; Rybina, Arina; Stephan, Holger; Storch, Golo; Wadepohl, Hubert (Journal of inorganic biochemistry, 2015)
The substitution of tetradentate bispidine ligands with rhodamine and cyanine dye molecules, coupled to an amine donor, forming an amide as potential fifth donor, is described. Bispidines are known to lead to very stable CuII complexes, and the coordination to CuII was expected to efficiently quench the fluorescence of dye molecules. However, at physiological pH the amide is not coordinated, as shown by titration experiments and crystallographic structural data of three possible isomers of these complexes. This may be due to the specific cavity shape of bispidines and the Jahn-Teller lability of the CuII center. While CuII coordination in aqueous solution leads to efficient fluorescence quenching, experiments show that the complex stabilities are not large enough for CuII sensing in biological media, and possibilities are discussed, how this may be achieved by optimized bispidine-dye conjugates.
Gesehen am 29.05.2020
Im Titel ist "II" in CuII hochgestellt